If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3y + 2x = 2(y + -2x) Reorder the terms: 2x + 3y = 2(y + -2x) Reorder the terms: 2x + 3y = 2(-2x + y) 2x + 3y = (-2x * 2 + y * 2) 2x + 3y = (-4x + 2y) Solving 2x + 3y = -4x + 2y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4x' to each side of the equation. 2x + 4x + 3y = -4x + 4x + 2y Combine like terms: 2x + 4x = 6x 6x + 3y = -4x + 4x + 2y Combine like terms: -4x + 4x = 0 6x + 3y = 0 + 2y 6x + 3y = 2y Add '-3y' to each side of the equation. 6x + 3y + -3y = 2y + -3y Combine like terms: 3y + -3y = 0 6x + 0 = 2y + -3y 6x = 2y + -3y Combine like terms: 2y + -3y = -1y 6x = -1y Divide each side by '6'. x = -0.1666666667y Simplifying x = -0.1666666667y
| 6(x+9)=8x+8-2x+46 | | 63(5x+4/9)=6(50x-1/3) | | 10+3n=14 | | 6x-9=6(x+9) | | 0.5(x+100)=0.58x-574 | | -16t^2+24t=0 | | 6x-4y=7 | | N/-2=8 | | -4=-10/86+8 | | (7x^3*(2x^2)^2)/(10x^5) | | 3.4x=2.6x+5.6 | | (x/9)=(x/10)-8 | | x/9=x/10-8 | | 100(2+x)=100 | | (x-1)3+64=0 | | f(x)=-2x^2+5x+40 | | 10(z+2)-2(z-2)=3(z-3)+4(z-1) | | 0.4(0.7-4x)=-1.1x | | 459x+1377-23=8x+160 | | R/-6=-4 | | x^6/5-729=0 | | 50=-2(23-y)+4(y-3) | | v^2+15v+56= | | 2(x+1)(x-1)-(2x+3)(x-2)=0 | | 12m=56+12m | | x^3-4x^2-x-10=0 | | 14x^2=16 | | 4(t+1)=6-1 | | (x+7)2=100 | | -64=-8v | | 18-4x+6=x+9 | | S-15=-15 |